Associations Between Latent Classes of Trauma Exposure and Minority Stressors and Substance Use Among Cisgender Sexual Minority Women. Issue 13 (July 2023) - Scheer, Jillian R.; Wall, Melanie M.; Veldhuis, Cindy B.; Ford, Jessie V.; Cascalheira, Cory J.; Helminen, Emily C.; Shaw, Thomas J.; Jaipuriyar, Virinca; Zaso, Michelle J.; Hughes, Tonda L.
Psychosocial stressors (e.g., minority stressors, trauma exposure) profoundly impact sexual minority women's (SMW's) risk of alcohol and other drug (AOD) use. However, research has not examined whether there are distinct typologies (i.e., patterns) of psychosocial stressors and whether these vary based on sociodemographic characteristics or are differentially associated with AOD outcomes (e.g., alcohol dependence) among SMW. This study aimed to identify latent classes of SMW reporting distinct typologies of psychosocial stressors and examine predictors and outcomes of latent classes of psychosocial stressors among SMW. Participants included a community sample of 602 SMW ( M age = 39.9, SD = 14.0; 74.0% lesbian; 37.4% White, 36.6% Black, 22.3% Latinx; 26.6% annual income ≤14, 999). Latent class analysis was used to identify typologies of psychosocial stressors. Regression analyses were employed to examine sociodemographic predictors and AOD outcomes of class membership. Three classes of psychosocial stressors emerged. Participants in Class 1 were likely to report relatively low adversity. SMW in Class 2, who reported childhood physical abuse (CPA), severe childhood sexual abuse, and adult physical assault, were vulnerable to discrimination and stigma consciousness. A distinct subgroup of SMW (Class 3) was at heightened risk of CPA, adult sexual assault (ASA), and stigma consciousness. Older SMW, Black SMW, and SMW with lower social support were more likely to be in classes characterized by higher adversity. Older SMW were at disproportionate risk of CPA and ASA. Different combinations of psychosocial stressors were uniquely associated with AOD outcomes. Findings underscore the importance of considering within-group heterogeneity in SMW's differential risk of psychosocial stressors and AOD outcomes. Routine screening of psychosocial stressors across several dimensions, brief interventions targeting AOD outcomes, and policies mitigating structural drivers of SMW's increased risk of trauma and minority stressors may be especially important for older SMW, Black SMW, and SMW who lack social support.